DEVELOPMENT OF NANO IN SITU GELS OF BEVACIZUMAB FOR THE TREATMENT OF OCULAR ANGIOGENESIS: IN VITRO ASSESSMENT OF ANTI-ANGIOGENESIS ACTIVITY AND MOLECULAR DOCKING ANALYSIS - NARAYANA, SOUMYA; AHMED, MOHAMMED GULZAR; NASRINE, ARFA (International Journal of Applied Pharmaceutics, 2023)
Objective: The present investigation aims to develop nano in situ gels of bevacizumab and evaluate their safety and efficacy. Methods: Nanoparticles were designed using the desolvation and double emulsion solvent evaporation technique. The hen’s egg test: chorioallantoic membrane (HET-CAM) assay was adopted to evaluate the anti-angiogenesis and irritancy potential of prepared nano in situ gel. Computational docking study carried out using glide module of Schrodinger software. Results: The FT-IR study showed no interaction between the components. The drug-loaded nanoparticle showed particle size in the range of 369±5.3 to 410±3.5, followed by PDI 0.41±0.1 to 0.73±0.1, and ζ–Potential-13±2.3 to-9±3.4. The entrapment efficiency of nanoparticles was found in between the range of 72.35±1.4 to 87.22±1.1, followed by loading efficiency of 8.81±0.3 to 12.78±0.7. The FE-SEM studies resulted in an irregular pattern of aggregated particles. The spherical shape of the particles was confirmed through the HR-TEM study. The nano in situ gel exhibited pH in the range of 7.2±0.2 to 7.3±0.1 followed by a viscosity of 325.2±8.7 to 498.7±5.8 mPa. s. CAM assays revealed the safety and anti-angiogenesis activity of the developed formulation. All different concentrations of in situ gels of bevacizumab showed a significant anti-angiogenic effect. The outcome of the molecular docking study revealed the well-binding capacity of bevacizumab with vascular endothelial growth factor (-7.325) and human serum albumin (-5.620) residues. Conclusion: The above outcomes improved our perception regarding the anti-angiogenic activity and safety of nano-in situ gels of bevacizumab. Overall, these findings denoted that implementing the current idea in the therapy of ocular angiogenesis might be a promising platform for better treatment.